Sky Captain and the world of tomorrow - Conran, Kerry, 1967-; Paltrow, Gwyneth, 1972-; Law, Jude, 1972-; Jolie, Angelina, 1975-; Ribisi, Giovanni, 1974-; Gambon, Michael; Adkins, Eric.; Shearmur, Edward; Paramount Pictures Corporation (Hollywood, Calif. : Paramount, 2005)
Circa 1939 ace city reporter Polly Perkins has noted the sudden disappearances of many of the world's most famous scientists. After the city falls under attack of giant flying robots, she decides to team up with her ex- boyfriend, aviation officer Joe 'Sky Captain' Sullivan and flys around the world in search of the evil mastermind, Dr. Totenkopf, whose plan it is to create a new world by destroying the one of today.
Originally released as a motion picture in 2004.
"Special collector's edition"--Container.
Director of photography, Eric Adkins ; animation director, Steven F. Yamamoto ; editor, Sabrina Plisco ; music, Edward Shearmur ; costume designer, Stella McCartney ; production and costume designer, Kevin Conran ; senior visual effects supervisor, Scott E. Anderson ; special photographic process, Stephen Lawes.
Gwyneth Paltrow, Jude Law, Angelina Jolie, Giovanni Ribisi, Michael Gambon, Bai Ling, Omid Djalili, Sir Laurence Olivier.
MPAA rating: PG; for sequences of stylized sci-fi violence and brief mild language.
DVD.
Keywords: Reporters and reporting -- Drama; Scientists -- Drama; Robots -- Drama; Video recordings for the hearing impaired; Feature films; Science fiction films